DOREMI (Dongeng Arek Milenial): Library Program for Introducing Culture to Children and Youth - Prajawinanti, Arin; Syafaah, Darisy; Mujib, Imam; Junia M., Nike Karlina (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
Libraries must embrace innovation, ensuring that users can easily access and enjoy the services offered. This research aims to assess the effectiveness of DOREMI (Millennial Arek Tales) services as a novel means of cultural introduction. Employing a quantitative approach with descriptive research, the study utilized non-probability sampling, involving 100 respondents. Research methods included observation, distribution of questionnaires, and documentation. The study found that the DOREMI Live Streaming Service Innovation Program (Fairy Tales of Millennials) at the Tulungagung Regency Regional Library adheres to all principles of program innovation, encompassing program objectives, socialization, observations, and effectiveness. A significant 64% of respondents agreed that the DOREMI program enhances information and motivates them to engage in reading, while an equal percentage found the program organized by the library to be interesting. Additionally, 74% strongly agreed that participating in the DOREMI service imparted moral messages from the stories. The services provided an engaging and entertaining platform for storytelling, contributing to the promotion of cultural diversity and heritage within society. This enriches people’s knowledge and understanding of various cultures. In conclusion, the services proved highly effective as a medium for introducing culture to the millennial generation in today’s era.